HealthTech Innovation in 2024: Romania’s Growing Ecosystem - Andreea DIMA; Rebeca POPA; Ariana-Anamaria CORDOȘ (Applied Medical Informatics)
This paper takes a brief look at the HealthTech startup scene in Romania in 2024 considering the global innovations such as Artificial Intelligence-driven diagnostics, biodegradable materials, and 3D printing for medical purpose. On the Romanian side, the paper presented how the local HealthTech ecosystem is quickly growing thanks to support from programs such as EIT Health that provide resources, mentorship, and global opportunities for startups. Challenges such as political instability, limited access to financial capital, and regulatory delays hinder ecosystem growth. To keep up with the ongoing transformation in health care, Romania must adapt by fostering new solutions and building teams that value multidisciplinary collaboration towards daily practice solutions.